Understanding Complexity: The Use of Simulation Games for Engineering Systems. (October 2015) - Bekebrede, Geertje; Lo, Julia; Lukosch, Heide
Complexity is increasingly tied into systems of societies, technologies and organizations. As these systems are characterized by non-linear interactions, it becomes more and more difficult to manage, educate, understand and predict their processes and outcomes. This symposium presents cases of a variety of simulation games that facilitate in these different types of systems; it also examines the theoretical challenges of the design of simulation games for such complex systems. The examples show how both computer-based and traditional board games can be used in various domains to analyze and design complex processes such as asset management, manufacturing procedures, railway infrastructure innovations, and land use development. The case studies presented in this symposium introduce simulation games as alternative solutions to complex organizational and even societal problems.